2017
DOI: 10.1590/1678-4162-9426
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da dexmedetomidina e do tramadol, associados ao midazolam, em gatas anestesiadas com isoflurano e submetidas à ovário-histerectomia

Abstract: Avaliação da dexmedetomidina e do tramadol, associados ao midazolam, em gatas anestesiadas com isoflurano e submetidas à ovário-histerectomia [Evaluation of dexmedetomidine and tramadol, associated with midazolam, in RESUMOObjetivou-se comparar as alterações cardiorrespiratórias e a analgesia pós-operatória promovidas pela dexmedetomidina e pelo tramadol, quando associados ao midazolam, em felinas. Para tal, foram selecionadas 18 gatas hígidas, divididas em dois grupos randomizados: GDM, tratadas com dexmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Comparing the mean baseline parameters, such as HR, f , SBP, DBP, and MBP, with other studies that evaluated these same baseline parameters in felines [ 18 20 ], no discrepancies were observed between them, suggesting that the animals were not overly stressed or agitated.…”
Section: Discussionmentioning
confidence: 74%
“…Comparing the mean baseline parameters, such as HR, f , SBP, DBP, and MBP, with other studies that evaluated these same baseline parameters in felines [ 18 20 ], no discrepancies were observed between them, suggesting that the animals were not overly stressed or agitated.…”
Section: Discussionmentioning
confidence: 74%
“…Another form of use is continuous infusion, and doses of 1, 3, and 5 µg/kg/h are known to promote adequate postoperative analgesia (19) . It is noteworthy that dexmedetomidine analgesia and duration are dose-dependent (18) , and analgesiometric studies suggest that both the intensity and duration of analgesia of α-2 adrenergic receptor agonists are dose-dependent (4) .…”
Section: Discussionmentioning
confidence: 99%
“…Ovariohysterectomy (OH) is one of the most frequently performed surgeries in veterinary medicine, with a mild to moderate degree of pain, requiring the use of analgesics as part of the therapeutic protocol (1,2) . For this, it is interesting to combine different drugs, for example, α-2-agonists and opioids, for a multimodal approach and effective analgesia (3,4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations of tramadol (2 mg/ kg IM) and midazolam (0.2 mg/kg IM) as pre-anesthetic protocol for OVH were compared with dexmedetomidine. The tramadol group had fewer secondary effects (nausea and vomits), a faster recovery time, and better cardiovascular stability than the alpha-2 adrenergic agonist [ 84 ]. Furthermore, given the absence of cardiorespiratory changes and physiological parameters within normal ranges, Evangelista et al [ 53 ] suggested that tramadol is a reliable perioperative drug for cats undergoing OVH at the recommended doses.…”
Section: Therapeutic Efficacy Of Tramadol In Catsmentioning
confidence: 99%